THE IMPORTANCE OF VIRAL DETECTION IN ORAL FLUIDS IN PATIENTS WITH PERIODONTAL DISEASE. REVIEW - Alexandru Flondor; Irina-Georgeta Sufaru; Maria-Alexandra Martu; Ionut Luchian; Liliana Pasarin; Vasilica Toma; Silvia Martu (Romanian Dental Association for Education, 2020)
The direct involvement of herpesviruses in the evolution of periodontitis can change the concepts of pathogenesis and disease management. A double periodontal infection of herpesviruses and pathogenic bacteria tends to be associated with more severe periodontitis than a periodontal infection involving only bacteria. Classical techniques in viral diagnosis use cell culture or antigenemia. These diagnostic techniques have been largely replaced by DNA and / or RNA-based tests, which possess superior technical performance and cost advantages. False-negative and false-positive PCR results are an inherent concern. Poor design of the PCR test, without optimization or validation of the PCR methodology, may lead to inaccurate findings and incompatible with those of other studies. The concept of viral infections of the diseased periodontium may introduce a new level of understanding of the importance of preventing and controlling periodontal disease for medical purposes